2016
DOI: 10.1038/srep28451
|View full text |Cite
|
Sign up to set email alerts
|

Critical Role of COI1-Dependent Jasmonate Pathway in AAL toxin induced PCD in Tomato Revealed by Comparative Proteomics

Abstract: Alternaria alternata f.sp. Lycopersici (AAL) toxin induces programmed cell death (PCD) in susceptible tomato (Solanum lycopersicum) leaves. Jasmonate (JA) promotes AAL toxin induced PCD in a COI1 (coronatine insensitive 1, JA receptor)-dependent manner by enhancement of reactive oxygen species (ROS) production. To further elucidate the underlying mechanisms of this process, we performed a comparative proteomic analysis using tomato jasmonic acid insensitive1 ( jai1), the receptor mutant of JA, and its wild typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 55 publications
0
11
0
1
Order By: Relevance
“…To date, the most recent high-throughput proteomics analyses were reported by Martin et al [5] and Kilambi et al [6], who identified 3625 and 5404 proteins, respectively. Zhang et al [7] recently reported the identification of more than 10 000 proteins from tomato leaves with a global FDR of 5%. In this work, we present an in-depth characterization of the tomato fruit proteome through an extensive fractionation of tomato pericarp protein extracts.…”
Section: Abstract: Ms / Plant Proteomics / Solanum Lycopersicum L / mentioning
confidence: 99%
See 2 more Smart Citations
“…To date, the most recent high-throughput proteomics analyses were reported by Martin et al [5] and Kilambi et al [6], who identified 3625 and 5404 proteins, respectively. Zhang et al [7] recently reported the identification of more than 10 000 proteins from tomato leaves with a global FDR of 5%. In this work, we present an in-depth characterization of the tomato fruit proteome through an extensive fractionation of tomato pericarp protein extracts.…”
Section: Abstract: Ms / Plant Proteomics / Solanum Lycopersicum L / mentioning
confidence: 99%
“…As our dataset represents one of the largest described for S. lycopersicum L. fruit, to evaluate the stringency of our analysis workflow we compared the proteins identified in our dataset to the data from Zhang et al who recently reported the identification of more than 10 000 proteins from tomato leaves [7]. However, to get an accurate comparison, we reanalyze Zhang et al data with our search parameters.…”
Section: Abstract: Ms / Plant Proteomics / Solanum Lycopersicum L / mentioning
confidence: 99%
See 1 more Smart Citation
“…Detoksifikasi toksin yang masuk ke jaringan tanaman terjadi melalui reduksi kelompok karbonil penting pada toksin oleh enzim ANDPH-dependent reductase yang diekspresikan oleh tanaman yang tahan sehingga toksin jadi kehilangan kemampuan aktifitasnya. Mekanisme detoksifikasi ini mirip dengan ketahanan berbagai tanaman seperti jagung, padi, sorgum dan tebu terhadap toksin Helmithosporium Carbonum (HC) yang dihasilkan oleh Cochliobolus carbonum (Zainudin et al, 2015), tanaman tembakau terhadap toksin Alternaria Alternate (AAL) yang dihasilkan oleh Alternaria alternata (Tsuge et al, 2013;Zhang et al, 2016) dan tanaman oat terhadap toksin Victorin yang dihasilkan oleh Chocliobolus victoriae (Sweat & Wolpert, 2007;Sweat et al, 2008).…”
Section: Figure 2 Average Of Leaf Wilting Intensity Of the Pn 1981 Gunclassified
“…The hormone jasmonate (JA) is involved with multiple biological functions, such as biotic and abiotic stress, seed germination, pollen development and cell senescence (Chini, Gimenez‐Ibanez, Goossens, & Solano, ; Wang, Liu, Niu, Timko, & Zhang, ; Zhang et al., ). Jasmonyl‐isoleucine (JA‐Ile) receptor COI1 (CORONATINE INSENSITIVE 1), a compound of the Skp‐Cullin‐F‐box (SCF) E3 ubiquitin ligase complex SCF COI1 , is a key regulator of the JA signalling pathway (Chini et al., ; Chung & Howe, ; Thines et al., ; Zhang, Bokowiec, Rushton, Han, & Timko, ).…”
Section: Introductionmentioning
confidence: 99%